Real world evidence of epidemiological trends, clinical presentation, and prognostic outcomes of multiple myeloma (2007-2021) - Elsabah, Hesham; El Omri, Halima; Habas, Elmukhtar; Taha, Ruba Y.; ElKourashy, Sarah A.; Ibrahim, Feryal; Nashwan, Abdulqadir J.; Kassem, Nancy; Ojha, Laxmi; Singh, Rajvir; Ghasoub, Rola; El Omri, Abdelfatteh (Frontiers in Medicine, 2024)
Background: Multiple myeloma (MM) is one of the most common hematological malignancies globally, and it is projected to increase in the coming years. The objective of this study was to determine the epidemiology, clinical features, and prognostic outcomes of patients with MM in the only tertiary cancer hospital in Qatar. Methods: Patients with symptomatic myeloma diagnosed at the National Center for Cancer Care and Research in Qatar between 2007 and 2021 were included. Data on demographics, laboratory work, bone marrow analysis, radiology, and given treatment were collected. Descriptive statistics, survival curves, and multivariable Cox regression were used to identify independent mortality risk factors. Results: During the study period of 15 years, a total of 192 patients were diagnosed with MM. The incident rate of myeloma cases in 2021 was 8 patients per million. The median age of patients was 57 years [range 22-88], with 68% being above the age of 50 years at diagnosis. The majority of patients were male (71%) and (85%) were expats. At the time of diagnosis,most patients [n=169 (88%)] had bone lesions, and 27% had extramedullary plasmacytoma. Anemia, hypercalcemia, and spinal cord compression were reported in 53%, 28%, and 7% of patients, respectively, at presentation. The monoclonal immunoglobulin subtypes were IgG, IgA, and free light chain in 52%, 16%, and 26% of patients, respectively. The overall median survival was 103 months (95% CI 71-135 months). In a multivariate cox-regression analysis for risk factors, only high serum calcium (≥ 2.7 mmol/L) was associated with increased mortality (HR: 2.54, 95% C.I.: 1.40-4.63, p = 0.002). Patients who received an autologous stem cell transplant (ASCT) had significantly better overall survival. Conclusion: In this comprehensive study of patients with MM treated in a country with a small and young general population, centralized hematology care, and free cancer care, we found a low but increasing incidence of MM and a good overall survival. Hypercalcemia was confirmed as a negative risk factor. ASCT had a significant positive impact on survival and should be provided to all patients eligible for this treatment, even in the era of novel agents.